Penerapan Sistem Pendukung Keputusan Berbasis Metode Pareto ABC dan Optimasi Kualitatif untuk Efisiensi Pengadaan Obat - Susilo Romadhon; Zaenal Mustofa (Lembaga Pengembangan Kinerja Dosen, 2024)
Drug procurement at Amandha pharmacy is still carried out with uncertain considerations, resulting in irregular scheduling, this will have an impact on inventory costs due to the accumulation of inventory in the warehouse or the absence of drug inventory, pharmacy managers have difficulty in making decisions for drug procurement, due to factors that must be considered, namely the number of drug item sales, investment and cost allocation. The purpose of this study is to create software with the application of the Pareto ABC method and qualitative optimization which will be one of the considerations in decision making in ordering drugs. In this new system, the number of drug procurements to be ordered is based on 3 values ​​as considerations, namely use value, investment value and critical index value, with reference to the Pareto ABC method having a class level divided into class A with an investment value of 70%, class B 20% and class C 10%, the system will provide recommendations as considerations for the agency in ordering drugs. The function of this research is as a consideration in solving problems and improving the quality of drug procurement. The results of the research are in the form of software for drug procurement decision support systems as a consideration in preparing a strategic ordering plan that supports increasing efficiency, effectiveness and benefits of the agency.